Primulina quanzhouensis, a new species of Gesneriaceae from Guangxi, China - Zou, Ling-Li; Wei, Jing; Fu, Jia-Xin; Pan, Bo; Wen, Fang (Phytotaxa, 2025)
A new species of Primulina, P. quanzhouensis, is illustrated and described from Quanzhou County, Guangxi Zhuangzu Autonomous Region, China. Morphologically, it is similar to P. yungfuensis, but it exhibits significant differences in having leaves nearly rounded to slightly oblate, cymes unbranched or 1-branched, usually 2-flowered or sometimes more and bracts elliptic. According to IUCN category and criteria, it is accessed to be Critically Endangered [CR B2ab(V)].